Screening and Characterisation of Silver Nanoparticles for the Prevention of Biofilm in Urinary Catheters - Meenakumari1, S.; D. Arunachalam2, Kantha; Sathesh Kumar2, A. (Asian Journal of Chemistry, 2013)
Biofilms are communities of microorganisms which are tradionally considered to result from adhesion and capsule formation by adherent to a surface microorganisms. The development of biofilm around the indwelling devices like catheters, stunts, pacemakers, intrauterine devices is a major threat in medical field. The synthesis of green nanoparticles using herbal plant extracts and characterization of the prevention or suppression of catheter related pathogens such as Pseudomonas aeruginosa, Klebsiella pneumonia, Enterococcus faecalis, Staphylococcus aureus and Coagulase Negative Staphylococci (CONS) under in vitro conditions are entirely new approach where no reports are available. In this present study attempts were made to characterize the antimicrobial properties of the green synthesized silver nano particles of two Indian Medicinal plants such as Aeglemarmelos and Saracaasocaagainst the urinary catheter pathogens. The green nanoparticles synthesized using the aqueous extracts of two Indian medicinal herbs were characterized through UV-VIS, SEM. The antimicrobial activities of the herbal plants against the pathogens present in the urinary catheters were studied byagar dilution method. Based on results of the in vitro studies a stimulation model will be constructed to verify the prevention of biofilm formation in bioreactors using a representative pathogen from the urinary catheters.